2006
DOI: 10.1002/art.21919
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of JNK by MKK‐7 in fibroblast‐like synoviocytes

Abstract: These data indicate that only MKK-7 is required for JNK activation in FLS after cytokine stimulation; however, other forms of cellular stress utilize MKK-4. Thus, JNK function might be modulated by targeting MKK-7 to suppress cytokine-mediated FLS activation while leaving other stress responses intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 28 publications
3
50
0
Order By: Relevance
“…JNK is thought to be important in extracellular matrix degradation. JNK is a critical MAPK pathway for IL-1-induced collagenase gene expression and regulation of MMP secretion in RASF [37][38][39]. Furthermore, JNK-1deficient osteoclast progenitors were unable to mature into bone-resorbing osteoclasts following exposure to receptor activator of nuclear factor-κB ligand (RANKL) [40].…”
Section: Discussionmentioning
confidence: 99%
“…JNK is thought to be important in extracellular matrix degradation. JNK is a critical MAPK pathway for IL-1-induced collagenase gene expression and regulation of MMP secretion in RASF [37][38][39]. Furthermore, JNK-1deficient osteoclast progenitors were unable to mature into bone-resorbing osteoclasts following exposure to receptor activator of nuclear factor-κB ligand (RANKL) [40].…”
Section: Discussionmentioning
confidence: 99%
“…JNK can be strongly activated in multiple cell types by LPS or inflammatory cytokines and regulates AP-1 transcription factor activity and the production of inflammatory cytokines (64,65). Previous studies demonstrated that MKK7, but not MKK4, is essential for IL-1-mediated JNK activation in cultured fibroblast-like synoviocytes (52). However, the functions of MKK4 in regulating the innate immune responses in the macrophages have not been fully defined.…”
Section: Discussionmentioning
confidence: 99%
“…1). Because JNK is typically activated by MKK4 and MKK7 and both MKKs are phosphorylated in rheumatoid synovium (Sundarrajan et al, 2003;Inoue et al, 2006), binding affinities of IQ-1S toward these kinases were also determined. However, IQ-1S demonstrated only a low binding affinity for MKK4 (K d approximately 2.2 mM) and there was no affinity for MKK7.…”
Section: Inhibition Of Collagen-induced Arthritis By Iq-1smentioning
confidence: 99%